MENINGKATKAN AKTIVITAS, KREATIVITAS, DAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL BRILIAN DI SEKOLAH DASAR - Nur Azizah, Wafa; Jannah, Fathul; Riandy Agusta, Akhmad; Sari, Raihanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this study is the low activity and creativity of students in the content of Natural Sciences (IPA) which causes not maximizing learning outcomes. The effort to overcome these problems is by applying the BRILIAN model. This study aims to describe the activities of educators, analyze the improvement of students' activities, creativity, and learning outcomes. This research is a Classroom Action Research (PTK) conducted with 4 meetings. The subjects of this study were fifth grade students of SDN Karang Mekar 4 Banjarmasin, with 26 students consisting of 11 boys and 15 girls. The research was conducted in the second semester of the 2023/2024 school year. This research uses a qualitative approach. The data taken is qualitative data obtained through observation of educator activities, learner activities and learner creativity, then using quantitative data for student learning outcomes obtained through written tests in groups and individually. Data analysis in this study used descriptive analysis techniques and was described in tables, graphs and interpretations with percentages. The results of this study indicate that the activities of educators increased from a score of 18 to 27 with "Very Good" criteria. Learner activity increased from a percentage of 27% to 96% with the criteria "Very Active". Learners' creativity increased from a percentage of 27% to 96% with the criteria "Very Creative". Classical learner learning outcomes from a percentage of 54% to 100% reached classical completeness. Based on the results of the study, it can be concluded that the use of the BRILIAN model can increase the activity, creativity, and learning outcomes of students. Keywords: Activity, Creativity, Learning Outcomes, BRILIAN Model